DEVELOPING CRITICAL THINKING THROUGH ENGLISH LANGUAGE INSTRUCTION - Mustafakulova Nilufar Bekzod qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Critical thinking has long been recognized as one of the most transferable and valuable cognitive skills a learner can acquire, yet its relationship to language instruction remains undertheorized and inconsistently practiced. This article investigates the extent to which English language instruction can serve as a productive site for the development of critical thinking skills, including analysis, inference, evaluation, and the construction of reasoned argument. Drawing on a systematic review of empirical studies, curriculum analyses, and practitioner accounts published between 2013 and 2024, the paper examines the pedagogical strategies most commonly associated with critical thinking outcomes in EFL and ESL contexts. Results indicate that task-based learning, Socratic questioning, argumentation-focused writing instruction, and literature-based discussion activities offer the strongest evidence base for fostering critical thought alongside linguistic development. However, the review also identifies significant challenges, including examination-oriented curricula, cultural variation in critical thinking norms, and insufficient teacher preparation. The discussion calls for a reconceptualization of English language teaching that treats critical thinking not as an optional enrichment activity but as a central and assessable dimension of communicative competence.